Positron Emission Tomography-Determined Hyperemic Flow, Myocardial Flow Reserve, and Flow Gradient—Quo Vadis? - Leucker, Thorsten M.; Valenta, Ines; Schindler, Thomas Hellmut (Frontiers in Cardiovascular Medicine, 2017)
Positron emission tomography/computed tomography (PET/CT) applied with positron-emitting flow tracers such as 13N-ammonia and 82Rubidium enables the quantification of both myocardial perfusion and myocardial blood flow (MBF) in ml/g/min for coronary artery (CAD) detection and characterization. The detection of a regional myocardial perfusion defect during vasomotor stress commonly identifies the culprit lesion or most severe epicardial narrowing, whereas adding regional hyperemic MBFs, myocardial flow reserve (MFR), and/or longitudinal flow decrease may also signify less severe but flow-limiting stenosis in multivessel CAD. The addition of regional hyperemic flow parameters therefore may afford a comprehensive identification and characterization of flow-limiting effects of multivessel CAD. The non-specific origin of decreases in hyperemic MBFs and MFR, however, prompts an evaluation and interpretation of regional flow in the appropriate context with the presence of obstructive CAD. Conversely, initial results of the assessment of a longitudinal hyperemic flow gradient suggest this novel flow parameter to be specifically related to increases in CAD-causes of epicardial resistance. The concurrent assessment of myocardial perfusion and several hyperemic flow parameters with PET/CT may indeed open novel avenues of precision medicine to guide coronary revascularization procedures that may potentially lead to a further improvement in cardiovascular outcomes in CAD patients.